ANALISIS PELAKSANAAN KETEPATAN IDENTIFIKASI PASIEN BERDASARKAN STANDAR SASARAN KESELAMATAN PASIEN DI RUMAH SAKIT SURYA INSANI PASIR PENGARAIAN - Ahmed Mawardi; Asriwati Asriwati; Jamaluddin Jamaluddin (STIKes Hang Tuah Pekanbaru, 2020)
Patient identification is one of the goals of patient safety at the hospital. This research is a qualitative descriptive study, aimed to analyze the implementation of the accuracy of patient identification at Surya Insani Hospital. Data collection was done by interview, observation, and document review. The informants were patient safety team, nursing manager, room head, registration officer, nurse, midwife, patient and their companion. The results showed that the implementation of patient identification at the Hospital was running but not in accordance with standards. Health worker knowledge as still lacking; the officer did not verify patient data; and the patient was not well educated regarding the implementation of patient identification that did not run well because of frequent employee changes, the lack of socialization provided to the officers, the compliance of officers at the SOP was still lacking, and there was no reporting of it. Suggestion for hospitals to control and prevent employee turnover intentions; the hospital patient safety team needs to disseminate the patient identification procedure; recording and reporting the implementation of the accuracy of patient identification; and the need to emphasize the officer's responsibility in explaining the importance of patient identification and the use of identity bracelets when installing it.